Effects of walking speed and age on the muscle forces of unimpaired gait subjects - Fliger, Carlos G. (2016)
Clinical gait analysis provides great contributions to the understanding of gait disorders and also provides a mean for a more comprehensive treatment plan. However, direct measures of muscle forces are difficult to obtain in clinical settings because it generally requires invasive techniques. Techniques of musculoskeletal modeling have been used for several decades to improve the benefits of clinical gait analysis, but many of the previous studies were focused on analyzing separately the muscle forces distribution of children or adult subjects with only one condition of walking speed. For these reason, the present study aims to enhance the current literature by describing the age and speed gait effects on muscle forces during walking. We used a musculoskeletal model with 23 degrees of freedom and 92 musculotendon actuators to represent 76 muscles in the lower extremities and torso. The computed muscle control algorithm was used to estimate the muscle forces from the kinematics and to adjust the model obtained in the residual reduction algorithm. We find that hamstrings has an important peak in the mid-stance phase in the adult group but this peak disappears in the children group with the same walking speed condition. Furthermore, the rectus femoris presents an increase in the muscle force during the pre- and mid-swing in concordance with the increment in the walking speed of subjects. This behavior could be associated with the role that the rectus femoris has in the acceleration of the knee joint. Finally, we show that the soleus is the muscle that perform the major force throughout the gait cycle regardless of age and walking speed.